Embryotoxicity of zinc oxide nanoparticles on Javanese medaka (Oryzias javanicus Bleeker, 1854) - Naweedullah, Amin (2021)
Zinc oxide nanoparticles (ZnO NPs) are widely applied in various industrial products such as cosmetics, pharmaceutical, and rubber production. However, this nanoparticle is classified as extremely toxic for the aquatic environment, particularly fish. Moreover, to date, there have been no systematic studies of the toxicity of ZnO NPs to the same species of organism in saltwater versus freshwater conditions, or during graded salinity changes. The objectives of this study are 1) to determine the median lethal concentration (LC50) of ZnO NPs for the embryos of Javanese medaka (Oryzias javanicus) in different types of water (ultra-pure, deionized and dechlorinated tap water), 2) to evaluate developmental toxicity of ZnO NPs by chronic exposure on the embryo of Javanese medaka, and 3) to assess the interactive effects of salinity and ZnO NPs by chronic exposure on the embryo of Javanese medaka. The experiments were conducted in a completely randomized design with three replicates for each concentration. The acute toxicity tests were conducted to determine the 96 h median concentration (LC50) of ZnO NPs for Javanese medaka embryos in different types of water. Results demonstrated the 96 h LC50 of ZnO NPs for Javanese medaka embryos were determined 0.6438 mg/L, 1.333 mg/L, and 2.251 mg/L in ultra-pure, deionize, and dechlorinated tap water, respectively. Chronic exposure of ZnO NPs on Javanese medaka’s embryos at concentration of 0-25 μg/L was also conducted for 21 days. The heart rate of exposed Javanese medaka embryos increased as the concentration of ZnO NPs increased and showed significantly higher heart rate when it compared with control at 5, 8 and 11 dpe. In general, the mortality of embryos increased and the hatching rates were decreased as the concentration of ZnO NPs were increased. Also, series of abnormalities such as low pigmentation, fin rot, spinal deformities, cranial oedema, yolk sac oedema, precordial oedema, and cranial facial were observed in treatment groups. Javanese medaka embryos were also exposed to 25, 50, and 100 μg/L of ZnO NPs in two different salinity levels (5 and 18 ppt) in this study. The results showed that the toxicity of ZnO NPs on Javanese medaka embryos decreased as salinity of suspension increased. For instance, in contrast to control, exposed embryos to ZnO NPs at 5 ppt showed significantly higher heart rates to 25, 50 and 100 μg/L of ZnO NPS at 5, 8, and 11 dpe. However, at 18 ppt significantly lower heart rate to 25, 50 and 100 μg/L of ZnO NPs were only observed at 5 dpe. In addition, mortality of exposed Javanese medaka embryos were increased by increasing concentration of ZnO NPs at both salinity level but in contrast to control, significantly higher mortality were observed at 5 ppt at the end of the experiment. Moreover, hatching of exposed embryos decreased as the concentration of ZnO NPs increased at both salinity level. Although, only significantly lower hatching rate were observed at 5 ppt when it compared to control. Furthermore, abnormalities such as low pigmentation, oedema, and tail malformation were observed in treatment groups at both salinity levels throughout the experiment, but abnormalities were more obvious at 5 ppt compared to 18 ppt. This study has revealed that ZnO NPs were extremely toxic to the embryo of Javanese medaka in different types of water, and there was a strong correlation between toxicity of ZnO NPs and salinity of suspension. The finding of this study can strengthen the creation of Javanese medaka as a model organism for tropical areas in aquatic nanoecotoxicological studies. Furthermore, the LC50 value is a valuable criterion for nanoecotoxicity; it is not a representative concentration of contaminants in aquatic environments, but it is essential for indicating the toxicity of certain pollutants. Although the concentrations of ZnO NPs in Malaysia aquatic ecosystem is not yet reported, the result of this showed that this hazardous chemical has the potential to have significant impacts on aquatic ecosystems and its living organisms even at environmental relevant concentration.